Sikap Negatif Bahasa Indonesia Siswa Kelas VIII SMP IT Aziziyah - Rosita, Dian; Herwandi (UIR PRESS, 2021)
Language attitude is a mental position or feeling towards one's own language or the language of others. This study aims to describe and analyze the negative attitude of Indonesian class VIII SMP IT Aziziyah. This research is a case study research that was carried out on February 04 - March 02, 2020. The subjects of this research were students of class VIII at SMP IT Aziziyah totaling 3 classes. The theory used by the author regarding Indonesian language attitudes is Sociolinguistics from (Chaer & Leoni, 2004) which discusses language attitudes. The data collection method used in this research is to use the method of observation and listening. Data collection techniques used are listening, recording and note-taking techniques. Data analysis techniques used to analyze the research are data reduction, data presentation, and drawing conclusions or verification. The results showed that the language attitude of the students of SMP IT Aziziyah, Tampan District, Pekanbaru City towards the Indonesian language in the conative aspect, namely a) language loyalty totaling 12 data, b) language pride totaling 14 data, c) awareness of language norms totaling 9 data so that the total number of data students' language attitude is 35 data.